2013
DOI: 10.3390/su5030997
|View full text |Cite
|
Sign up to set email alerts
|

Focal Areas for Measuring the Human Well-Being Impacts of a Conservation Initiative

Abstract: Within conservation, the need to measure the impacts on people from conservation initiatives such as projects and programs is growing, but understanding and measuring the multidimensional impacts on human well-being from conservation initiatives is complex. To understand the constituent components of human well-being and identify which components of well-being are most common, we analyzed 31 known indices for measuring human well-being. We found 11 focal areas shared by two or more indices for measuring human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 35 publications
0
36
0
1
Order By: Relevance
“…Humans are dependent upon the services provided by nature and unless we effectively account for the range of values from ecosystems in our efforts to protect the environment, we cannot sustain human well-being [1,2]. Land use and land cover change (LUCC) is a driver of global change that directly influent the status and integrity of ecosystems and in last term its capacity to supply ecosystem services [3].…”
Section: Introductionmentioning
confidence: 99%
“…Humans are dependent upon the services provided by nature and unless we effectively account for the range of values from ecosystems in our efforts to protect the environment, we cannot sustain human well-being [1,2]. Land use and land cover change (LUCC) is a driver of global change that directly influent the status and integrity of ecosystems and in last term its capacity to supply ecosystem services [3].…”
Section: Introductionmentioning
confidence: 99%
“…Going further, a growing literature on well-being has emphasized the need for context-specific indicators of well-being for diverse peoples (Dodge et al 2012, La Placa et al 2013, Leisher et al 2013. Sometimes called the "biocultural" approach (Sterling et al in press), this work emphasizes a more fine-grained analysis of the characteristics of well-being as defined by people in different environments.…”
Section: Well-being and Conservation: Definitions And Measurementmentioning
confidence: 99%
“…In the case of social cohesion, an additional challenge is the categorization of this concept. Leisher et al [70] found that sixteen human well-being indices accounted for social cohesion; the authors categorized this concept on the basis of social relationships, community, connectedness, intergroup cohesion, and social capital. Others have accounted for social capital and cohesion and have assigned an intrinsic value to social cohesion (i.e., the desired ends), such as trust or cultural norms, as well as an instrumental value to social capital [36].…”
Section: Implications Of Adapting the Cascade Model To Social Cohesiomentioning
confidence: 99%
“…Similarly, Barnes-Mauthe et al [71] measured social cohesion as a dimension of social capital. Some have suggested that local conditions should be the basis for defining social capital indicators, as the context highly determines the results [70,72]. Here, we applied the dimensions proposed by Kearns and Forrest [66] to interrelate the potential benefits from UA with the creation of social cohesion values.…”
Section: Implications Of Adapting the Cascade Model To Social Cohesiomentioning
confidence: 99%